PENGARUH SANKSI PAJAK, PELAYANAN APARAT PAJAK, DAN PEMAHAMAN PERATURAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK DENGAN PREFERENSI RISIKO SEBAGAI VARIABEL MODERASI (Studi Kasus Pada UMKM Yang Terdaftar di KPP Pratama Semarang Barat) - Ani Sulistiyani, 13.05.52.0089; Srimindarti, Ceacilia (Students Journal of Accounting and Banking, 2017)
This study examined the influence of tax penalty, Tax officer service, and Tax rule comprehension for Against Taxpayer Compliance with Risk Preference Being a Moderation Variable (Case Study On UMKM Listed In KPP Pratama West Semarang).Â The sampling method using conveniece sampling, the technique of determining the sample based on the ease of encounter. The influence variables or effect analyzed by using multiple regression analysis.Â The results showed that tax penalty Resource positive and significant impact on Against Taxpayer Compliance, Tax officer service Resource negative and insignificant impact on Against Taxpayer Compliance, Tax rule comprehension Resource positive and significant impact on Against Taxpayer Compliance, Risk Preference to moderating the tax penalty influence of Against Taxpayer Compliance, Risk Preference moderating the Tax officer service influence of Against Taxpayer Compliance, and Risk Preference moderating the Tax rule comprehension.Keywords: Tax Penalty, Tax Officer Service, and Tax Rule Comprehension, Against Tax Payer Compliance and Risk Preference